Decreased surfactant lipids correlate with lung function in chronic obstructive pulmonary disease (COPD) - Agudelo, Christina W.; Kumley, Britta K.; Area-Gomez, Estela; Xu, Yimeng; Dabo, Abdoulaye J.; Geraghty, Patrick; Campos, Michael; Foronjy, Robert; Garcia-Arcos, Itsaso (PloS one, 2020)
Smoke exposure is known to decrease total pulmonary surfactant and alter its composition, but the role of surfactant in chronic obstructive pulmonary disease (COPD) remains unknown. We aimed to analyze the compositional changes in the surfactant lipidome in COPD and identify specific lipids associated with pulmonary function decline. Bronchoalveolar lavage (BAL) fluid was obtained from 12 former smokers with COPD and 5 non-smoking, non-asthmatic healthy control volunteers. Lipids were extracted and analyzed by liquid chromatography and mass spectrometry. Pulmonary function data were obtained by spirometry, and correlations of lung function with lipid species were determined. Wild-type C57BL/6 mice were exposed to 6 months of second-hand smoke in a full-body chamber. Surfactant lipids were decreased by 60% in subjects with COPD. All phospholipid classes were dramatically decreased, including ether phospholipids, which have not been studied in pulmonary surfactant. Availability of phospholipid, cholesterol, and sphingomyelin in BAL strongly correlated with pulmonary function and this was attributable to specific lipid species of phosphatidylcholine with surface tension reducing properties, and of phosphatidylglycerol with antimicrobial roles, as well as to other less studied lipid species. Mice exposed to smoke for six months recapitulated surfactant lipidomic changes observed in human subjects with COPD. In summary, we show that the surfactant lipidome is substantially altered in subjects with COPD, and decreased availability of phospholipids correlated with decreased pulmonary function. Further investigation of surfactant alterations in COPD would improve our understanding of its physiopathology and reveal new potential therapeutic targets.